A study of essential oil from an invasive Piper aduncum L. - Wibawa, I Putu Agus Hendra; Saraswaty, Vienna; Kuswantoro, Farid; Andila, Putri Sri; Wardhani, Putri Kesuma; Tirta, I Gede; Sujarwo, Wawan (Jurnal Biologi Udayana, 2019)
An invasive Piper aduncum is a plant species that potentially produces essential oil. The study aims to determine the percentage, phytochemical compounds, and anti-fungal properties of essential oil produced from the leaves and fruits of Piper aduncum. The study showed that the leaves and fruits of P. aduncum contain 0.30% and 0.33% of essential oil, respectively. Apiol is the most abundant phytochemical compound obtained in essential oil of leaves and fruits of P. aduncum with 57.10% and 66.31%, respectively. We conclude that essential oil obtained in this study is able to inhibit the growth of both Aspergillus niger and Cladosporium sp. but not for Fusarium oxysporum and Fusarium solani.